Analysis of the online payment point system of banking to customer satisfaction in PDAM Tirtanadi brach Medan Sunggal - Syaiful Bahri (Proceedings of AICS - Social Sciences, 2017)
PDAM Tirtanadi is one of the local government enterprise that provider drinking water service to the public. The services provided under the PPOB system still disrupt the network technology system and there is a decrease in income, so as not to reach the level of customer satisfaction of PDAM Tirtanadi Medan Sunggal Branch. The purpose of this research is to test and analyze the influence of PPOB system on customer satisfaction at PDAM Tirtanadi Medan Sunggal Branch. The type of this research is descriptive quantitative and the nature of research using descriptive explanatory. This research uses accidental sampling method. The population in this study as many as 3030 customers and samples used 97 customers in PDAM Tirtanadi Medan Branch Sunggal. Data analysis using simple linear regression analysis. The results showed that the PPOB system has a positive and significant influence on customer satisfaction. This shows that the better PPOB system provided by PDAM Tirtanadi Medan Sunggal Branch will increase customer satisfaction.